Building Character of Leadership - Nazifah Husainah (Greenation International Journal of Tourism and Management, 2023)
The objective of this research was to examine the impact of leadership and compensation on employee motivation, as well as their implications on the performance of cooperative employees in Karawang, both individually and collectively. The research employed a descriptive and verificative method, utilizing a survey as the primary tool. The study focused on 330 employees of cooperatives as respondents. Data analysis was conducted using the LISREL 8.80 program, employing the Structural Equation Model (SEM). The findings of the study indicate that: 1) leadership and compensation have a significant positive effect on motivation, accounting for 52% of the variance (R2 = 0.52). 2) leadership, compensation, and motivation all have a positive and significant impact on employee performance, accounting for 75% of the variance (R2 = 0.75). Among the variables examined, motivation was found to have the most influence on performance, while compensation was identified as the most influential factor on motivation. Based on the research findings, it is recommended that efforts be made to enhance employee performance in cooperatives in the Karawang district through the improvement of employee motivation. This can be achieved by fostering strong relationships between employees and members, co-workers, and management, as well as by increasing compensation levels, which should encompass salary conformity, incentives, food allowance, transportation allowance, and by improving leadership qualities, including supportive behaviors such as providing employment opportunities, favorable working conditions, conflict resolution, and boosting morale.